2017
DOI: 10.1177/1010428317711140
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 variations and functions in lung adenocarcinoma

Abstract: Lung cancer ranks as the first most common cancer and the first leading cause of cancer-related death in China and worldwide. Due to the difficulty in early diagnosis and the onset of cancer metastasis, the 5-year survival rate of lung cancer remains low. JAK2 has emerged as pivotal participant in biological processes, often dysregulated in a range of cancers. Recently our study found that JAK2 might play an important role in lung cancer pathogenesis. While our understanding of JAK2 in the onset and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The JAK/STAT signaling pathway is a downstream pathway of cytokine signaling, which regulates cell differentiation, proliferation, and apoptosis and plays an important role in the occurrence and development of tumors 33 . Compared with adjacent nontumor tissues, JAK2 mRNA expression was upregulated in LUAD tissues, and overexpression of JAK2 induced A549 cell proliferation, migration, and invasion capabilities 34 . Xu and Lu 35 demonstrated that high expression of STAT3 or p‐STAT3 is a powerful predictor of poor prognosis in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The JAK/STAT signaling pathway is a downstream pathway of cytokine signaling, which regulates cell differentiation, proliferation, and apoptosis and plays an important role in the occurrence and development of tumors 33 . Compared with adjacent nontumor tissues, JAK2 mRNA expression was upregulated in LUAD tissues, and overexpression of JAK2 induced A549 cell proliferation, migration, and invasion capabilities 34 . Xu and Lu 35 demonstrated that high expression of STAT3 or p‐STAT3 is a powerful predictor of poor prognosis in patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…33 Compared with adjacent nontumor tissues, JAK2 mRNA expression was upregulated in LUAD tissues, and overexpression of JAK2 induced A549 cell proliferation, migration, and invasion capabilities. 34 Xu and Lu 35 demonstrated that high expression of STAT3 or p-STAT3 is a powerful predictor of poor prognosis in patients with NSCLC. In our study, PYCR1 knockdown was found to inhibit the proliferation and migration of LUAD cells, while increasing the expression of JAK2, STAT3, and p-STAT3.…”
Section: Pycr1 Knockdown Affected the Jak/stat Signaling Pathway Inmentioning
confidence: 99%
“…For instance, JAK2 is frequently mutated in myeloproliferative disorders . Dysregulated JAK2 influences the proliferation and aggression of lung adenocarcinoma cells . To our best knowledge, dysregulation of JAK2 in several cancer types, such as colorectal cancer, gastric cancer and thyroid cancer, is mainly caused by the up‐ or downregulation of upstream miR‐375 .…”
Section: Introductionmentioning
confidence: 99%
“…25 Dysregulated JAK2 influences the proliferation and aggression of lung adenocarcinoma cells. 26 To our best knowledge, dysregulation of JAK2 in several cancer types, such as colorectal cancer, gastric cancer and thyroid cancer, is mainly caused by the up-or downregulation of upstream miR-375. [27][28][29] However, whether the JAK2 expression in HCC is also mediated by miR-375 remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of JAK2 in myeloproliferative neoplasms is well-established (Bader and Dreiling, 2019, Mata et al, 2007, Panani, 2009, Xu et al, 2014). It is also associated with other malignancies like leukaemia (Singh et al, 2018) and cancers of skin (Pritchard et al, 2018), lung (Li et al, 2017, Xu et al, 2017), and stomach (Judd et al, 2014).…”
Section: Introductionmentioning
confidence: 99%